Production of Routine Formulae by Chinese Learners of Thai:: An Interlanguage Pragmatic Study - Sripunvoraskul, Radarat; Panpothong, Natthaporn (Journal of Letters, 2024)
Routine formulae are expressions used repeatedly in specific situations. While the use of routine formulae is common knowledge for native speakers, second-language learners often find it challenging. This research aims to examine the production and communication problems associated with routine formulae used by Chinese learners of Thai. The study adopts the perspective of interlanguage pragmatics and employs DCT for data collection. Participants include 33 Chinese learners of Thai, ranging from B2 to C2 proficiency levels, and 30 native speakers of Thai. In-depth interviews were also conducted with 30 native speakers. The results reveal that even though they are intermediate to advanced L2 learners, their usage of routine formulae appears to have two main problems. Firstly, learners use routine formulae significantly less frequently than native speakers. Secondly, they also use expressions rarely adopted by native speakers, especially in situations aimed at expressing emotions or goodwill. Some of these differences may lead to various types of communication problems, including issues related to intention, politeness and interpersonal relationships, suitability for interlocutors, and naturalness. Additionally, the findings reflect the influence of the learners’ mother tongue on their language use.